Group portrait of the attendees of the Toyon 2 Youth Institute meeting at Monte Toyon - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Toyon 2 Youth Institute meeting, held August 29 to September 05, 1953 at Monte Toyon in Aptos, California. Some of the attendees can be seen holding signs and banners that read: "San Jose Delta Chi First Church," "Alameda," and "San Mateo."